Sentence comprehension and working memory in Malay adults - Yazmin Ahmad Rusli; Montgomery, James (Penerbit Universiti Kebangsaan Malaysia, 2020)
Studies on sentence comprehension have centered on understanding the intersection between language and cognition. The aim of the current study was to examine the association between complex sentence comprehension and working memory (WM) in Malay adults. We predicted that WM storage (as indexed by performance on a WM listening span task) would be invoked during the processing of complex Malay sentences (object relatives), but not simple sentences (subject-verb-object). Sixty adults participated in the study; 30 Malay- and 30 English native speakers. The experimental tasks were developed in both Malay and English versions for both groups respectively. Participants completed (i) two sets of sentence comprehension tasks (whereby comprehension was determined via selection of the agent of the sentence), and (ii) a conventional WM listening span task. Tasks were designed to be structurally similar in terms of length (within the language) and meaning (across both languages). Both groups performed significantly better on the comprehension of simple sentences as compared to complex sentences and obtained similar mean scores on the WM listening span task. For Malay comprehenders, WM storage did not significantly correlate with comprehension of simple sentences as well as complex sentences. The same correlation pattern was also revealed for the English comprehenders. Our predictions were partially borne out. Findings suggest that participants’ comprehension of complex sentences did not invite WM storage, as it would seem that both Malay and English participants were still able to comprehend these complex sentences without having to tax their WM capacity. Although we anticipated a relation, the absence of such an association is not entirely unexpected. Potential explanations are discussed in this article.